춘파 적응성 내도복 다수성 겉보리‘호향’ - 김양길(Yang-Kil Kim), 윤영미(Young-Mi Yoon), 박종호(Jong-Ho Park), 김경호(Kyong-Ho Kim), 강천식(Chon-Sik Kang), 박태일(Tae-il Park), 오세관(Sea-kwan Oh) (Korean journal of breeding, 2020)
A new six-rowed covered barley cultivar ‘Hohyang’ with spring sowing adaptability, lodging tolerance, and high yield was developedfrom the cross between ‘Saegangbori’ and ‘Durubori’ by the National Institute of Crop Science, RDA, Korea, in 2016. It has a compactspike and long awn, and its growth habit (vernalization requirement) was classified as group II. The averaged heading date was April 21,which was 1 day earlier than that of the control varietal, ‘Olbori’. The culm length was 78 cm, which was similar to that of ‘Olbori’; however,‘Hohyang’ has a stronger lodging tolerance. Its spike length was 4.7 cm, 655 spikes/m2, 55 grains/spike, and 31.9 g for 1,000 grains. Italso showed similar winter hardiness and a superior resistance to barley yellow mosaic virus (BaYMV) compared to that of ‘Olbori’. ‘Hohyang’was well adapted to spring sowing conditions from March 6 to April 3. Regarding quality, ‘Hohyang’ had the same protein and β-glucancontent as ‘Olbori’, but higher polyphenol content than the control cultivar. The yield of ‘Hohyang’ in the regional yield trial was 6.68 ton/hain upland zones, and 5.06 ton/ha in paddy fields, which were 6% and 15% higher than those of the control cultivar, respectively. If thereis rain during the fall planting season, ‘Hohyang’ is suitable for sowing and cultivation in spring (Registration No. 7374). KCI Citation Count: 2